Development of nano titanium dioxide modified carbon paste electrode for determination of chloramphenicol in vaname shrimp (Litopenaeus vannamei) pond water by cyclic voltammetry - Zahro, Nafisatuz; Setiarso, Pirim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Chloramphenicol is an antibiotic that has activity against aerobic, anaerobic, and fungal bacteria and is often used in vaname shrimp farming pond water. Behind its usefulness, chloramphenicol has side effects for health, such as aplastic anemia, bone marrow suppression, stomach intestinal disorders, and optical and peripheral neuropathy. This study aims to determine the ability of carbon paste electrodes modified with nano titanium dioxide to detect chloramphenicol levels in vaname shrimp pond water by cyclic voltammetry. This research has successfully made an electrochemical sensor as a nano titanium dioxide-modified carbon paste electrode to detect chloramphenicol in vaname shrimp pond water samples. Nano titanium dioxide used as a modifier in carbon paste electrodes was characterized by XRD (X-Ray Diffraction) and FTIR (Fourier Transform Infrared), while the study of electrochemical characteristics using cyclic voltammetry method. The electrochemical sensor that has been made is a nano titanium dioxide-modified carbon paste electrode that can detect chloramphenicol in vaname shrimp pond water using the cyclic voltammetry method.